2019
DOI: 10.1007/s00432-019-03019-6
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial infusion chemotherapy versus isolated upper abdominal perfusion for advanced pancreatic cancer: a retrospective cohort study on 454 patients

Abstract: PurposeThe treatment of pancreatic carcinoma remains a challenge as prognosis is poor, even if confined to a single anatomical region. A regional treatment of pancreatic cancer with high drug concentrations at the tumor site may increase response behaviour. Intra-arterial administration of drugs generates homogenous drug distribution throughout the entire tumor volume.MethodsWe report on treatment outcome of 454 patients with advanced pancreatic carcinoma (WHO stage III: 174 patients, WHO stage IV: 280 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 27 publications
2
26
0
2
Order By: Relevance
“…Although we routinely perform isolated hypoxic perfusion for various cancers, we rarely see patients with gynecological tumors, primarily treated by gynecologic oncologists. The presented cases demonstrated excellent results in advanced cervical cancer, which is often the case with arterial chemotherapy and isolated hypoxic perfusion in other tumor types [ [16] , [17] , [18] , [19] ].…”
Section: Discussionmentioning
confidence: 98%
“…Although we routinely perform isolated hypoxic perfusion for various cancers, we rarely see patients with gynecological tumors, primarily treated by gynecologic oncologists. The presented cases demonstrated excellent results in advanced cervical cancer, which is often the case with arterial chemotherapy and isolated hypoxic perfusion in other tumor types [ [16] , [17] , [18] , [19] ].…”
Section: Discussionmentioning
confidence: 98%
“…With regard to preoperative chemotherapy, Karl et al reported the usefulness and low toxicity of chemotherapy administered by intra-arterial infusion, including isolated abdominal perfusion [ 22 ]. However, our patient also had an abdominal aortic aneurysm with type 2 endoleak despite her previous EVAR, so catheterization was considered to be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…stages III and IV) SAE NS 0% mOS: IAIC 5–21 Syst chemo 2.7–14 Liu [ 30 ] 2016, R IAIC Catheter, NS 235 NS NS mOS 7 (incl. stages III and IV) Rosemurgy [ 31 ] 2017, NS IAIC Catheter, CTA 20 10 SAE in 20 pts 0% 1 yr 60% 2 yr 43% Aigner [ 32 •] 2019, R IAIC ± embolization vs. UAP Catheter, NS 174 NS AE or SAE 0% mOS: IAIC 8 UAP 12 Qiu [ 33 ] 2019, R IAIC Catheter, NS 31 1% 0% mOS 5.3 …”
Section: Locoregional Ablation Brachytherapy Chemotherapy and Immunotherapymentioning
confidence: 99%
“…employed for the treatment of hepatic tumors [98], but some literature has also been published on its use in pancreatic cancer [9,[30][31][32][33]. The exact tumor location and its supplying arteries determine through which vessels the chemotherapeutic infusion will be delivered.…”
Section: Immunomodulation After 125 I Seed Implantationmentioning
confidence: 99%